ANALYSIS OF FACTORS INFLUENCING CONSUMERS IN PURCHASE DECISIONS OF LOCAL FRUITS IN BIREUEN DISTRICT (Case Study of Bireuen Traditional Market Consumers) - Gina Silmi; Mawardati Mawardati; Irada Sinta (Jurnal Mahasiswa Agribisnis, 2023)
Local fruits are fruits that are cultivated by farmers in each region in Indonesia. Consumption of local fruit in Indonesia is still relatively low. This condition is due to the lack of public interest in consuming local fruit. The level of community consumption of local fruit is influenced by consumer behavior in making decisions to buy local fruit. This research aims to analyze the factors that influence consumers in purchasing decisions of local fruit in the traditional market of Bireuen Regency. The results of this research using multiple linear regression analysis model obtained the equation Y = -2.101 + 0.297X1 + 0.429X2 + 0.364X3. The value of the coefficient of determination (Adjust R2) is 0.704 or equal to 70.4%. The percentage influence of individual factors, environmental influences, and marketing strategies can explain local fruit purchasing decisions of 70.4%, the remaining 29.6% is influenced by other variables outside the model that are not included in this study. The result of the F-test and t-test simultaneously and partially aspects of individual factors, environmental influences, and marketing strategies have a significant effect on local fruit purchasing decisions at the Bireuen Regency Traditional Market